THE IMPLEMENTATION OF E-GOVERNANCE IN IMPROVING PUBLIC SERVICES AT THE MEDAN DENAI SUB-DISTRICT OFFICE MEDAN CITY - Sabina Azira Balqis Siregar; Teuku Alfiady; Aflia Riski; Ti Aisyah; Muhammad Hasyem (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The implementation of E-Governance in improving public services at the Medan Denai District Office, Medan City, represents a digital transformation effort aimed at creating a transparent, accountable, and efficient government through information technology. However, its application at the district level has not yet been fully optimized. This study aims to describe the implementation of E-Governance at the Medan Denai District Office and to identify the factors inhibiting its effectiveness. The research employs a qualitative approach using primary and secondary data collected through observation, interviews, and documentation. Data were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. This study applies George C. Edward III’s policy implementation theory, which emphasizes four variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that E-Governance implementation at the Medan Denai District Office remains suboptimal. Information technology has improved service efficiency but is not yet fully integrated. Transparency is limited due to the lack of accessible public information, while accountability mechanisms such as complaint and reporting systems remain manual. The main obstacles include limited human resource capacity, inadequate technological infrastructure, weak inter-stakeholder communication, and a bureaucratic structure that does not fully support digital systems. Strengthening human resources, improving infrastructure, and optimizing digital systems are necessary to enhance public service quality.